Supply and Property Management Office Procurement Section a systems procedure study - Alipio, Ma. Theresa D.; Di, Nerissa C.; Lopez, Rassen M.; Ong, Jocelyn C.; Traya, Lloyd Apollo C. (College of Engineering, 1990)
The group has chosen the Supply and Property Management Office (SPMO) of the University of the Philippines for their Systems and Procedures study. This division has three main sections, namely, Purchasing and Requisitioning, Utilization and Disposal sections. It was agreed upon to concentrate on the Purchasing and Requisitioning Section. Areas considered are the forms flow, work distribution, work relationships and systems flow processes. Problem areas were also discovered. One major problem that needs consideration is the indifference of the different requisitioning units regarding the authority of the SPMO to procure materials for them. They assume that a lot of red tape has been happening and as a consequence, they tend to disregard the services of the SPMO and proceed on their own. When they ask the Vice Chancellor for Administration, Professor Ernesto Santos, to permit them to reimburse their purchases, the Vice Chancellor, in turn, reprimands the SPMO for not taking the responsibility of purchasing for the particular unit. Complications, then, arise. The group faced slight difficulties during this study. Drastic changes regarding certain rules, policies or procedures cannot be implemented because the SPMO is a government unit. Changes done to it would be carried to all government systems and this is quite improbable for the time being. Elimination of certain forms and their copies, reassignment of tasks to different employees to balance their workload and validation of the written standard practices compared to the actual procedures have all been presented to make the system more efficient and more productive. If these specifications are given the opportunity to be implemented, there is a great possibility that the SPMO services would be more reliable, more effective and more productive.